Porous nanofibrous poly(l-lactic acid) scaffolds supporting cardiovascular progenitor cells for cardiac tissue engineering. (15th October 2015) - Liu, Qihai; Tian, Shuo; Zhao, Chao; Chen, Xin; Lei, Ienglam; Wang, Zhong; Ma, Peter X.
Graphical abstract: Abstract: Myocardial infarction (MI) is the irreversible necrosis of heart with approximately 1.5 million cases every year in the United States. Tissue engineering offers a promising strategy for cardiac repair after MI. However, the optimal cell source for heart tissue regeneration and the ideal scaffolds to support cell survival, differentiation, and integration, remain to be developed. To address these issues, we developed the technology to induce cardiovascular progenitor cells (CPCs) derived from mouse embryonic stem cells (ESCs) towards desired cardiomyocytes as well as smooth muscle cells and endothelial cells. We fabricated extracellular matrix (ECM)-mimicking nanofibrous poly(l -lactic acid) (PLLA) scaffolds with porous structure of high interconnection for cardiac tissue formation. The CPCs were seeded into the scaffolds to engineer cardiac constructs in vitro. Fluorescence staining and RT-PCR assay showed that the scaffolds facilitated cell attachment, extension, and differentiation. Subcutaneous implantation of the cell/scaffold constructs in a nude mouse model showed that the scaffolds favorably supported survival of the grafted cells and their commitment to the three desired lineages in vivo. Thus, our study suggested that the porous nanofibrous PLLA scaffolds support cardiac tissue formation from CPCs. The integration of CPCs with the nanofibrous PLLA scaffolds represents a promising tissue engineering strategy for cardiac repair. Statement of Significance: Myocardial infarction is the irreversible necrosis of heart with approximately 1.5 million cases every year in the United States. Tissue engineering offers a promising strategy for cardiac repair after MI. However, the optimal cell source for heart tissue regeneration and the ideal scaffolds to support cell survival, differentiation, and integration, remain to be developed. To address these issues, we developed porous nanofibrous PLLA scaffolds that mimic natural extracellular matrix to support cardiac tissue formation from CPCs. The integration of CPCs with the nanofibrous PLLA scaffolds represents a promising tissue engineering strategy for cardiac repair.